2018
DOI: 10.1002/brb3.991
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical effect of baclofen on social behavior in the fragile X syndrome mouse model

Abstract: IntroductionFragile X syndrome (FXS) is a common monogenetic cause of intellectual disability, autism spectrum features, and a broad range of other psychiatric and medical problems. FXS is caused by the lack of the fragile X mental retardation protein (FMRP), a translational regulator of specific mRNAs at the postsynaptic compartment. The absence of FMRP leads to aberrant synaptic plasticity, which is believed to be caused by an imbalance in excitatory and inhibitory network functioning of the synapse. Evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Arbaclofen has indeed been shown to normalize protein synthesis rates as well as a variety of physiological and behavioral phenotypes in FMR1 KO mice (Henderson et al, 2012 ; Silverman et al, 2015 ; Sinclair et al, 2017a ). However, clinical trials with arbaclofen have proved unsuccessful (Berry-Kravis et al, 2017 ) and recent animal studies found that chronic baclofen treatment can actually result in exacerbation of FXS phenotypes, potentially due to drug tolerance development (Zeidler et al, 2018 ). Drug tolerance development may also limit the effectiveness of other potential FXS therapies, like mGluR5 inhibitors (Stoppel et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Arbaclofen has indeed been shown to normalize protein synthesis rates as well as a variety of physiological and behavioral phenotypes in FMR1 KO mice (Henderson et al, 2012 ; Silverman et al, 2015 ; Sinclair et al, 2017a ). However, clinical trials with arbaclofen have proved unsuccessful (Berry-Kravis et al, 2017 ) and recent animal studies found that chronic baclofen treatment can actually result in exacerbation of FXS phenotypes, potentially due to drug tolerance development (Zeidler et al, 2018 ). Drug tolerance development may also limit the effectiveness of other potential FXS therapies, like mGluR5 inhibitors (Stoppel et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Paradoxically, clinical trials suggest that treatment with the GABA B R agonist baclofen improves irritability and social responsiveness in people with FXS and ASD; however, these results are mixed [ 50 52 ]. Moreover, baclofen can cause adverse side effects, including hyperactivity and anxiety in FXS patients [ 53 55 ]. Our results raise the question of why GABA B R signaling is required for synaptogenesis and antidepressant efficacy in WT mice yet prohibitive in Fmr1 KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…While clinical trials demonstrate that treatment with the GABAB agonist baclofen improves irritability and social responsiveness in people with FXS and ASD, these results are mixed [41][42][43] . Additionally, baclofen can cause adverse side effects, including hyperactivity and anxiety [44][45][46] . These data, in light of our results, raise the question as to why GABABR signaling is required for synaptogenesis and antidepressant efficacy in WT mice, yet prohibitive in Fmr1 KO mice.…”
Section: Discussionmentioning
confidence: 99%